UJI AKTIVITAS ANTIBAKTERI INFUSA DAUN SIRSAK (Annona muricata L.) SECARA in Vitro TERHADAP Staphylococcus aureus ATCC 25923 dan Escherichia coli ATCC 35218 SERTA PROFIL KROMATOGRAFI LAPIS TIPISNYA - Yeni, Yeni Dianita; Djannah, Sitti Nur; Nurani, Laela Hayu (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2010)
Background: A research has been done to test the In vitro antibacterial activities of sirsak leaf(Annona muricata L.) infuse toward Staphylococcus aureus ATCC 25923 and Escherichia coliATCC 35218 to analyze its thin layer chromatography profile. This research done to observe theantibacterial activity from sirsak leaf infuse.Method: A test on the antibacterial activity was done by using liquid dilution method. Theconcentration infuse in sterile destilate water using to test the antibacterial activity toward S.aureus were 100%, 95%, 90%, 85%, 80%, and 75% w/v, while toward E. coli were 100%, 90%,80%, 70%, 60%, and 50% w/v. To detect Chemical contains of the sirsak leaf infuse wereidentified using Screening method of Phytochemistry and Thin Layer Chromatography (TLC).Result: The result showed that the Minimum Bacterial Concentration (MBC) of sirsak leaf infuseS. aureus were 85% w/v, while E. coli could not be show antibacterial activity until 100% w/vconcentration. The Minimum Inhibition Concentration (MIC) could not be identified by the liquiddilution because the mixture were turbid and the colour is dark brown. Screening method ofPhytochemistry use tube-test and Thin Layer Chromatography showed that the infuse containflavonoid, poliphenol, and alkaloid.Conclusion: Infuse of sirsak leaf (Annona muricata L.) has antibacterial activity againstStaphylococcus aureus ATCC 25923 and Escherichia coli ATCC 35218 profil infuse. Thin LayerChromatography showed that the infuse contain flavonoid, poliphenol, and alkaloid.Keyword: Antibacterial, sirsak leaf, chromatography